Epidemiological profile of acquired syphilis in women in the state of Goiás between 2016 and 2021 (Research, Society and Development, 2022)
Acquired syphilis is a chronic sexually transmitted disease caused by Treponema pallidum, a bacterium of the spirochete group, its transmission occurs through contaminated biological material, either through sexual intercourse, contact with skin wounds or blood transfusion. It affects about 701,883 people in Brazil, 278,300 of which are female. In Goiás, 6,958 cases of syphilis acquired in women were recorded. This study aimed to analyze the epidemiology of acquired syphilis in women in the state of Goiás. Therefore, a cross-sectional and descriptive study was carried out, through the study of scientific articles, detailing the secondary data available in the Department of Informatics of the SUS (TABNET/DATASUS), with the variables: gender, age group, ethnicity, period of time and location. It was observed that, between the years 2016 and 2021, there was, in general, an increase in cases in women, with great importance in the age group from 15 to 59 years of age and significantly present in all races, realizing a need strengthening public policies on sex education for the population.